CHECK THE ATTACHMENT FOR COMPLETE QUESTION
Answer:
We can show that ΔABC is congruent to ΔA'B'C' by a translation of 2 unit(s) Left and a Reflection across the x axis.
Step-by-step explanation:
We were given triangles ABC and A'B'C' of which were told are congruents,
Now we can provide the coordinates of A and A' from the given triangles ΔABC and ΔA'B'C' ,if we choose a point of A from ΔABC and A' from ΔA'B'C' we have these coordinates;
A as (8,8) and A' (6,-8) from the two triangles.
If we shift A to A' , we have (8_6) = 2 unit for that of x- axis
If we try the shift on the y-coordinates we will see that there is no translation.
Hence, the only translation that take place is of 2 units left.
It can also be deducted that there is a reflection
by x-axis to form A'B'C' by the ΔABC.
BEST OF LUCK
Select correct answer
Answer:
x1=1
x2= -4
x3= (2 + 5i)
x4= (2 - 5i)
Step-by-step explanation:
STEP 1-
Find the roots of the first term.
(x^2 + 3x -4)=0
Then group the terms that contain the same variable, and move the constant to the opposite side of the equation.
(x^2 + 3x)=4
Complete the square. Remember to balance the equation by adding the same constants to each side.
(x^2 + 3x + 1.5^2)=4 + 1.5^2
(x^2 + 3x + 1.5^2)=6.25
Rewrite as perfect squares
(x + 1.5)^2=6.25
Square root both sides.
(x + 1.5) = (+/-)2.5
x= -1.5(+/-)2.5
x= -1.5 + 2.5 = 1
x= -1.5 + 2.5= -4
so the factored form of the first term.
(x^2 + 3x + 4) = (x - 1) (x + 4)
STEP 2-
Find the roots of the second term
(x^2 - 4x + 29)= 0
Group terms that contain the same variable, and move the constant to the opposite side of the equation
(x^2 - 4x)= -29
Complete the square. Remember to balance the equation by adding the same constants to each side
(x^2 - 4x + 4) = - 29 + 4
(x^2 -4x + 4) = -25
Rewrite as perfect squares
(x - 2)^2 = -25
Remember that
i = square root of -1
Square root both sides
(x - 2) = (+/-)5i
x= 2 (+/-)5i
x= 2 + 5i
x= 2 - 5i
so the factored form of the second term is
(x^2 - 4x + 29) = (x - (2 + 5i))(x - (2 - 5i))
STEP 3-
Substitute the factored form of the first and second term in g(x)
g(x) = (x-1)(x + 4)(x- (2+ 5i))(x- ( 2-5i)
there for you have your answers
Reflexive Property
Symmetric Property
Definition of Midpoint
Help quickly
Answer:
Definition of congruence
Step-by-step explanation:
According to this
If two sides are equal then they are ought to be congruent.
Here
CD is equal to EF
Hence they are congruent
Based on the Definition of Congruence in mathematics, if two line segments are of equal lengths, then they are said to be congruent. So if CD = EF, then CD is congruent to EF (CD ≅ EF).
In this context, if CD = EF, then CD is indeed congruent to EF, written as CD ≅ EF.
This is based on the Definition of Congruence in mathematics, specifically geometry, which states that two objects (in this case, line segments) are congruent if they have the exact same size and shape, or, for line segments, the same length. So, if the lengths of two line segments are equal (CD = EF), then they are congruent (CD ≅ EF).
#SPJ2
Answer: 9 houses
Step-by-step explanation:
Step 1:
Since 2/3 of the houses were sold last month, 1/3 of them were left.
45 * 1/3 = 15 houses left last month
Step 2:
Since 2/5 of the remaining houses were sold this month, 3/5 of them were left
15 * 3/5 = 9 houses left to be sold
there's your answer hope this helps :)
Answer:
It is in the tenths place
Step-by-step explanation:
In the number 9.365, 3 is in the tenths place.